Dogsled team carrying food supplies outside the North American Transportation and Trading Co. offices, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Winter scene in Dawson Y.T.". Klondike Gold Rush.